Adsorption of Quercetin, Kaempferol and Luteolin on Surface-Modified Polytetrafluoroethylene Films - Gaohong Wang; Yanjuan Liu; Xinyi Huang; Duolong Di (Adsorption Science & Technology)
We studied the adsorption of three flavonoids on polytetrafluoroethylene (PTFE) film. The PTFE film was first treated with sodium naphthalene solution to improve the hydrophilicity of its surface and then modified by coating with dopamine using a simple self-assembly approach. The PTFE film thus prepared was used for adsorption of three flavonoids, namely, quercetin, kaempferol and luteolin. The adsorption capacity of the treated PTFE film that was not further modified by dopamine was also evaluated. The characteristics of the two materials (coated and non-coated) were studied using X-ray photoelectron spectroscopy, scanning electron microscopy and Fourier transform-infrared spectroscopy. The difference in adsorption capacity between the two materials was mainly due to the different functional groups introduced in these materials, which show difference in their ability to form hydrogen bond with the analytes. The number of hydroxyl groups in the analytes and the ability of the analytes to form intramolecular hydrogen bond are the two factors that affect the adsorption capacity of the adsorbates.